YOUNG GENERATION CONSUMER PREFERENCES FOR LOCAL AND IMPORTED FOOD PRODUCTS IN BAKU - Mammadov, Niyamaddin (My University, 2026)
This research explores young people's preferences between locally produced and imported food products in Baku and highlights the key determinants shaping consumers' choices. Relying on the Theory of Planned Behavior, consumer ethnocentrism, and the country-of-origin effect, this paper aims to test eight hypotheses about the effect of price, quality, freshness, trust, brand and packaging, support of local economy, safety, and country of origin on the preferences of consumers towards local food in contrast to imported products. In order to gather information about the topic, an online structured questionnaire was developed and distributed to 110 young consumers aged 18 to 35 years old, with 106 valid questionnaires obtained after the data were processed. The study uses descriptive statistics, Cronbach's alpha reliability test, exploratory factor analysis, Spearman's rank-order correlation, multiple linear regression, and ordinal logistic regression in the analysis of the data. According to the results, 45.7 percent of young consumers choose local food items; however, they exhibit significant category-specific asymmetric behavior, as local food is dominant among fresh food while imported products are prevalent among processed food products and beverages. Out of eight tested hypotheses, four have been supported: quality of imported food (the strongest determinant, positively predicting preference for imports), freshness of local food, trust in domestic companies, and support of local economy. The effect of country-of-origin has shown no aggregate effect due to the symmetric balancing of cognitive and normative components. Age is the only variable that shows significance, and the 8 group of 18 to 22-year-old people constitutes a separate sub-segment. This study contributes to country-of-origin research by exploring it in the context of South Caucasus and provides some recommendations for the producers and policymakers in Azerbaijan.
Keywords: consumer behavior; local food; country-of-origin effect; consumer ethnocentrism; young consumers; Azerbaijan